Entry Denied: Japan’s Border Restrictions in the Time of the COVID-19 Emergency - Nicola Costalunga (Dve Domovini, 2021)
With the outbreak of SARS-CoV-2 and the resulting COVID-19 pandemic, Japan adopted controversial policies to contain the virus. Unlike many highly developed countries, it enacted strict policies banning entry through its borders to all non- Japanese citizens regardless of their residency status. The further peculiarity is that these measures equalized low-skill and high-skill foreign workers, affecting them identically. Along with describing how the emergency has been handled in relation to foreign nationals, this article highlights how pre-existing socio-cultural dynamics of differentiation between “insiders” and “outsiders” have evolved in response to the pandemic.